Increasing levels of wild-type CREB up-regulates several activity-regulated inhibitor of death (AID) genes and promotes neuronal survival - Tan, Yan-Wei; Hoffmann, Tina; Bading, Hilmar (BMC neuroscience, 2012)
Background: CREB (cAMP-response element binding protein) is the prototypical signal-regulated transcription factor. In neurons, it is the target of the synaptic activity-induced nuclear calcium-calcium/calmodulin dependent protein kinase (CaMK) IV signaling pathway that controls the expression of genes important for acquired neuroprotection as well as other long-lasting adaptive processes in the nervous system. The function of CREB as a transcriptional activator is controlled by its phosphorylation on serine 133, which can be catalyzed by CaMKIV and leads to the recruitment of the co-activator, CREB binding protein (CBP). Activation of CBP function by nuclear calcium-CaMKIV signaling is a second regulatory step required for CREB/CBP-mediated transcription. Results: Here we used recombinant adeno-associated virus (rAAV) to increase the levels of wild type CREB or to overexpress a mutant version of CREB (mCREB) containing a serine to alanine mutation at position amino acid 133 in mouse hippocampal neurons. Increasing the levels of CREB was sufficient to boost neuroprotective activity even under basal conditions (i.e., in the absence of stimulation of synaptic activity). In contrast, overexpression of mCREB increased cell death. The ratio of phospho(serine 133)CREB to CREB immunoreactivity in unstimulated hippocampal neurons was similar for endogenous CREB and overexpressed wild type CREB and, as expected, dramatically reduced for overexpressed mCREB. A gene expression analysis revealed that increased expression of CREB but not that of mCREB in hippocampal neurons led to elevated expression levels of bdnf as well as that of several members of a previously characterized set of Activity-regulated Inhibitor of Death (AID) genes, which include atf3, btg2, gadd45β, and gadd45γ. Conclusions: Our findings indicate that the expression levels of wild type CREB are a critical determinant of the ability of hippocampal neurons to survive harmful conditions. Increasing the levels of wild type CREB can, even without inducing synaptic activity, increase pro-survival gene expression and strengthen the neurons’ neuroprotective shield. The observed degradation of CREB protein following NMDA treatment of hippocampal neurons suggests that the known CREB shut-off associated with extrasynaptic NMDA receptor-induced excitotoxicity is followed by CREB proteolysis.